PENGEMBANGAN POTENSI DIRI DALAM PEMBELAJARAN SELAMA PANDEMI COVID 19 (STUDI KEPUSTAKAAN BUKU “MALAS TAPI SUKSES” KARYA FRED GRATZON) - Muhammad Fauzy Emqi; Riantina Fitra Aldya (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
This study aims to determined self-potential in learning during the COVID-19 pandemic, through a literature study of a work entitled "The Lazy But Successful” by Fred Gratzon in 2010, where data will be collected and then analyzed based on a matrix from Moltke. The results showed that self-potential development can be done through several types of ways. Type A (mentally blunt and physically lazy) can be given simple tasks to allow for idea discovery, Type B (intelligent and energetic) can handle the details of things because of his accuracy, Type C (mentally blunt but energetic) needs to maximize physical activity with supervision extra, and type D (smart but lazy) can be a leader because it can easily find the simplest way that is easiest.